STRATEGI MENINGKATKAN KESADARAN HAK PRIVASI DALAM PENGGUNAAN LAYANAN ONLINE DALAM ERA DIGITAL - Wiraguna, Sidi Ahyar (LPPM Universitas Bina Bangsa, 2024)
In the growing digital age, the use of online services has become an integral part of daily life. The convenience and benefits offered by online services, there are also concerns about personal data privacy. Law No. 11 of 2008 on ITE article 26 paragraph 1: